2008
DOI: 10.1021/bi701699a
|View full text |Cite
|
Sign up to set email alerts
|

The Q-Loop of DrrA Is Involved in Producing the Closed Conformation of the Nucleotide Binding Domains and in Transduction of Conformational Changes between DrrA and DrrB

Abstract: DrrA and DrrB proteins form an ATP-dependent efflux pump for doxorubicin and daunorubicin in Streptomyces peucetius. DrrA, the catalytic subunit, forms a complex with the integral membrane protein DrrB. Previous studies have provided evidence for strong interaction between these two proteins, which was found to be critical for binding of ATP to DrrA and for stability of DrrB. Chemical cross-linking experiments carried out previously showed that in the resting state of the complex DrrA and DrrB are in contact w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 42 publications
(129 reference statements)
1
27
0
Order By: Relevance
“…the conformational transition of the Q loop and the coordination of this transition with the conformational changes of transmembrane subunits and NBDs (16). Similarly, it was suggested that the interaction of the Q loop in DrrA with the N-terminal cytoplasmic tail of DrrB, which is a transmembrane subunit, is involved in transmitting conformational changes between DrrA and DrrB (30). The X-ray structure of the fully assembled maltose transport system showed that the Q loops of MalK are in close proximity to the transmembrane subunit MalFG (24).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…the conformational transition of the Q loop and the coordination of this transition with the conformational changes of transmembrane subunits and NBDs (16). Similarly, it was suggested that the interaction of the Q loop in DrrA with the N-terminal cytoplasmic tail of DrrB, which is a transmembrane subunit, is involved in transmitting conformational changes between DrrA and DrrB (30). The X-ray structure of the fully assembled maltose transport system showed that the Q loops of MalK are in close proximity to the transmembrane subunit MalFG (24).…”
Section: Discussionmentioning
confidence: 97%
“…The key factor affecting the function of the NukFEG system needs to be determined. Recently, mutational studies of the Q loop have been carried out while studying DrrA, an NBD of an ABC transporter involved in self-resistance to anticancer antibiotics (doxorubicin and daunorubicin) (30). Nonconservative mutations of the Q loop (Q88S and Q88N) resulted in great reductions in the resistance levels; however, the Q88E mutation retained the resistance to a high degree.…”
Section: Discussionmentioning
confidence: 99%
“…Doxorubicin Resistance Assay-Doxorubicin resistance assays were carried out as described earlier (23). Briefly, the indicated plasmids were transformed into E. coli N43 cells, which are doxorubicin-sensitive.…”
Section: Methodsmentioning
confidence: 99%
“…ATP Bindng Assay-Photolabeling of DrrA with [␣-32 P]ATP was carried out in membranes containing wild type DrrAB or DrrAB bearing mutations in DrrA (23). The ATP binding assay was carried out in a 100-l reaction system containing buffer A, 0.1 mg of membrane protein, 10 M ATP (pH7.5), 10 Ci of [␣-32 P]ATP, 35 M doxorubicin, and 5 mM MgCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Using gene fusions, a topology model has been proposed for DrrB, consisting of eight membrane-spanning segments with both N and C termini in the cytoplasm (164). Cysteine cross-linking revealed a motif within the N-terminal tail of DrrB that may be a modified version of the EAA motif present in ABC importers (236,392). These two components are biochemically coupled and are thought to form an efflux pump (236,237).…”
Section: Class 3 Abc Systems That Are Probably Not Importersmentioning
confidence: 99%